PENGARUH PENYULUHAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN MAHASISWA KORPS SUKARELA PALANG MERAH INDONESIA TENTANG TRAUMA TULANG SERVIKAL DI STIKES HUTAMA ABDI HUSADA TULUNGAGUNG - Berlian Yuli Saputri; Ketjuk Herminaju; Ria Anggraini; Dwi Retnowati (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
College is a center of education, development and dissemination of knowledge. According to the WHO in 2011 spinal cord injury occurred in 30,000 patients each year in the United States and nearly 40% -50% lead to severe symptoms, and sometimes cause death, it is because of lack of information and understanding of what it's trauma of the cervical spine and how the handling initially. Given this research aimed to investigate the effect of health education to increase student knowledge and students are expected to get the right information about the trauma of the cervical spine. The design used in this study is the One-group pre-post Test Design by comparing the results of pre-test and post-test without making a comparison with the influence imposed on other groups. The study population was mostly student volunteer corps PMI in STIKES Hutama Abdi Husada Tulungagung using total sampling technique with a total of 40 respondents. Retrieving data using a questionnaire. Then the data is processed by the technique Editing, Coding, Scoring and Tabulating. Then analyzed with a statistical test wilcoxon. The results showed that there is influence of health education to increase student knowledge PMI volunteer corps in STIKES Hutama Abdi Husada Tulungagung indicated with p = 0.000 and α = 0.05, which means the value (p≤0,05). Therefore, researchers found that the provision of health information is very important, including to students who study in the health field it proved useful to improve one's knowledge / students in this study were medical students